2011
DOI: 10.7748/nm2011.10.18.6.27.c8718
|View full text |Cite
|
Sign up to set email alerts
|

Using real time patient feedback to introduce safety changes

Abstract: Holding regular safety briefings and debriefings has improved safety and the patient experience at one trust. The approach was piloted in an elective orthopaedic inpatient setting and includes obtaining real time patient feedback. The comments are themed, which enables staff to introduce service changes to rectify any problems. Staff using the tools have adopted the process as part of their working schedule. The authors discuss the advantages of using such an approach, which they believe can be introduced in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…UK examples of such interventions include the Real Time Patient Feedback initiative in the Royal Devon and Exeter NHS Foundation Trust40 and the Patient Toolkit and patient incident reporting strategies currently being developed by the Yorkshire Quality and Safety Research Group 41. US examples include The Joint Commission's ‘Speak Up’ campaign, and the ‘Condition H’ help line for patient-activated rapid response calls at the University of Pittsburgh Medical Center.…”
Section: Discussionmentioning
confidence: 99%
“…UK examples of such interventions include the Real Time Patient Feedback initiative in the Royal Devon and Exeter NHS Foundation Trust40 and the Patient Toolkit and patient incident reporting strategies currently being developed by the Yorkshire Quality and Safety Research Group 41. US examples include The Joint Commission's ‘Speak Up’ campaign, and the ‘Condition H’ help line for patient-activated rapid response calls at the University of Pittsburgh Medical Center.…”
Section: Discussionmentioning
confidence: 99%
“…There are some exceptions to this -for example Ward and Armitage (2012) explore the extent of safety incident reporting among patients in a hospital setting, Weingart et al (2004) report on lessons learnt from an intervention to prevent adverse drug events, and Larsen et al (2011) describe the use of patient feedback in real time to improve safety. In general, though, the published evidence focuses on attitudes and expectations rather than on the opportunities for patient involvement in patient safety and the results of these.…”
Section: The Literaturementioning
confidence: 96%
“…Another review of the literature on methods of reporting adverse events (King et al 2010) showed that higher numbers of incidents were reported when open-ended questions were used and when patients were asked about their own experiences. One approach to incorporating patient experience into organizational systems has been proffered by Larsen et al (2011), who described a safety briefing process, designed by nursing staff, whereby patients are asked a set of key questions at the beginning of each shift about their care (Larsen et al 2011). This was accompanied by a set of comment cards given to patients by a 'neutral' member of staff for patients to complete, which were then collected and used at debriefing meetings at the end of the shift.…”
Section: Patient Feedback and Error Reportingmentioning
confidence: 99%
“…By highlighting what needs to be improved and how these improvements can be achieved in a planning process, improvement ideas can be tested and visualized on a small scale through the PDSA cycle: Plan, Do, Study, and Act [14]. Studies show that the PDSA methodology increases adherence to evidence-based practice that improve quality of care and patient safety [2,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, health systems must be economically sustainable, in line with good clinical practice, and developed in consultation with the patient [1][2][3]. Evidence-based care is based on three approaches: patient needs and desires, staff skills and experience, and recent evidence in this research field [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%